2021
DOI: 10.1111/psyp.13817
|View full text |Cite
|
Sign up to set email alerts
|

The effects of vibrotactile masking on heartbeat detection: Evidence that somatosensory mechanoreceptors transduce heartbeat sensations

Abstract: The field of cardioception has received considerable attention from the scientific community for close to fifty years (Brener & Ring, 2016;Jones, 1994). Heartbeat sensations are caused by pulsatile mechanical stimuli generated by ventricular contraction. However, the types of mechanoreceptors and the afferent pathways (interoceptive, somatosensory, exteroceptive) responsible for transducing heartbeat sensations and conveying the information to the brain have yet to be identified. Despite this, measurements of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…Given the existence of reports showing the involvement of somatosensory mechanoreceptors in cardioception (Macefield, 2003; Knapp-Kline, Ring, Emmerich, & Brener, 2021), we also included a control task, namely, the grating orientation task, which is a well-established measure of tactile acuity (Johnson & Phillips, 1981). By including this task, we could assess to what extent the potential difference in the ability to detect heartbeats is specific to cardiac interoceptive accuracy itself and not due to the influence of superior tactile acuity of blind participants (e.g., Goldreich & Kanics, 2003; Alary et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Given the existence of reports showing the involvement of somatosensory mechanoreceptors in cardioception (Macefield, 2003; Knapp-Kline, Ring, Emmerich, & Brener, 2021), we also included a control task, namely, the grating orientation task, which is a well-established measure of tactile acuity (Johnson & Phillips, 1981). By including this task, we could assess to what extent the potential difference in the ability to detect heartbeats is specific to cardiac interoceptive accuracy itself and not due to the influence of superior tactile acuity of blind participants (e.g., Goldreich & Kanics, 2003; Alary et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there remains some coherence with the hypothesis of right cerebral hemisphere engagement in the representation of heartbeat sensations attributable to peripheral cardiovascular asymmetries 20 , 49 , 50 . Confidence in heartbeat sensations may also be affected by pre-existing beliefs and biases arising from the participants’ understanding of anatomy (including knowledge that the heart is placed largely in the left part of the chest) and by quasi-interoceptive somatosensory pathways from the chest wall or the skin (see 51 ) , which may afford great perceptual precision relative to viscerosensation. We have some evidence to support this second explanation, notably that higher confidence was associated with reduced dispersion of the sampling location; thus, better spatial precision that may suggest a greater somatosensory contribution.…”
Section: Discussionmentioning
confidence: 99%
“…We have some evidence to support this second explanation, notably that higher confidence was associated with reduced dispersion of the sampling location; thus, better spatial precision that may suggest a greater somatosensory contribution. Indeed, it has been shown that the somatosensory (exteroceptive) pathway that gathers information from the skin and from Pacinian and non-Pacinian somatosensory mechanoreceptors located on the chest wall also contributes to the spatial precision of heartbeat perception 21 , 51 . For example, when participants are asked to focus on heartbeats, not only the insula but also the somatosensory cortices are activated 20 , 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Other issues with such methods include evidence that the performance at heartbeat counting or detection tasks seem to be influenced by other factors such as prior knowledge, heart rates, beliefs, practice, and even experimental instructions (e.g., Ross & Brener, 1981;Whitehead & Drescher, 1980;Ring & Brener, 1996;Ring et al, 2015;see Zamariola et al, 2018;Zimprich et al, 2020, Ainley et al, 2020Corneille et al, 2020 for an extensive debate on the issues related to heartbeat tasks). Additionally, from the physiological point of view, the heartbeat signal itself can be problematic as it represents a multimodal, rather "noisy" signal, given the concurrent vascular and muscle contractions, which give rise to a cascade of other bodily signals (e.g., activation of tactile mechanoreceptors and volume of blood ejected at each heartbeat, Knapp-Kline, Ring, Emmerich & Brener, 2021;Azzalini, Rebollo & Tallon-Baudry, 2019).…”
Section: The Problematic Assessment Of Interoceptionmentioning
confidence: 99%
“…Other issues with such methods include evidence that the performance on heartbeat counting or detection tasks seems to be influenced by other factors such as prior knowledge, heart rates, beliefs, practice, and even experimental instructions (e.g., Ring & Brener, 1996 ; Ring et al, 2015 ; Ross & Brener, 1981 ; Whitehead & Drescher, 1980 ; for an extensive debate on the issues related to heartbeat tasks, see Ainley et al, 2020 ; Corneille et al, 2020 ; Zamariola et al, 2018 ; Zimprich et al, 2020 ). In addition, from a physiological point of view, the heartbeat signal itself can be problematic because it represents a multimodal, rather “noisy” signal given the concurrent vascular and muscle contractions that give rise to a cascade of other bodily signals (e.g., activation of tactile mechanoreceptors and volume of blood ejected during each heartbeat; Azzalini et al, 2019 ; Knapp-Kline et al, 2021 ). Thus, it is challenging to know whether participants are feeling the heartbeat signal per se or whether they are using other bodily strategies to complete heartbeat detection or counting tasks (e.g., changes in respiration, tensing muscles, feeling pulsations in the fingertips; Murphy et al, 2019 ; Ross & Brener, 1981 ; Whitehead & Drescher, 1980 ).…”
Section: The Problematic Assessment Of Interoceptionmentioning
confidence: 99%